2010
DOI: 10.1002/mrm.22687
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory bellows revisited for motion compensation: Preliminary experience for cardiovascular MR

Abstract: For many cardiac MR applications, respiratory bellows gating is attractive because it is widely available and not disruptive to or dependent on imaging. However, its use is uncommon in cardiac MR, because its accuracy has not been fully studied. Here, in 10 healthy subjects, the bellows and respiratory navigator (NAV) with the displacement of the diaphragm and heart were simultaneously monitored, during single-shot imaging. Furthermore, bellows-gated and NAV-gated coronary MRI were compared using a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 17 publications
2
83
0
Order By: Relevance
“…Although respiratory belts do not directly measure the most dominant respiratory motion component of the abdomen (i.e., foot–head translation), we found good correlation between the self‐navigator signals describing foot–head signal variations and the respiratory belts. This is also confirmed by recent studies that have shown that respiratory belts yield very robust respiratory motion information . In addition, we only used the respiratory belt to bin the acquired data.…”
Section: Discussionsupporting
confidence: 64%
“…Although respiratory belts do not directly measure the most dominant respiratory motion component of the abdomen (i.e., foot–head translation), we found good correlation between the self‐navigator signals describing foot–head signal variations and the respiratory belts. This is also confirmed by recent studies that have shown that respiratory belts yield very robust respiratory motion information . In addition, we only used the respiratory belt to bin the acquired data.…”
Section: Discussionsupporting
confidence: 64%
“…The respiratory bellows is an alternative means of measuring respiratory position during MR scanning (Santelli et al, 2011). This consists of an air filled bag, which is wedged between the subject's abdomen or chest and a firm surface such as an elasticated belt.…”
Section: Scalar Surrogate Datamentioning
confidence: 99%
“…The most commonly used external respiratory monitoring device in cardiovascular MRI is the respiratory bellows [31,32], which measures pressure differences between the abdomen and a tightly wrapped belt to establish whether the respiratory cycle is in inspiration or expiration. Other techniques to perform respiratory motion estimation with external devices include measuring the electric impedance between ECG leads [33] or the more recently developed ultra wideband electromagnetic sensor [34].…”
Section: Respiratory Motion Estimationmentioning
confidence: 99%